Distal enlargement of the optic nerve sheath in the hyperacute stage of intracerebral haemorrhage. Issue 2 (1st August 2010) - Školoudík, David; Herzig, Roman; Fadrná, Táňa; Bar, Michal; Hradílek, Pavel; Roubec, Martin; Jelínková, Monika; Šaňák, Daniel; Král, Michal; Chmelová, Jana; Heřman, Miroslav; Langová, Kateřina; et al.
Abstract : Aims: Optic nerve sheath diameter (ONSD) enlargement is detectable in patients with increased intracranial pressure. The aim was to detect an enlargement of the ONSD using optic nerve sonography in patients with acute intracerebral haemorrhage (ICH) within 6 h of the onset of symptoms. Methods: Thirty-one acute ICH patients, 15 age-matched acute ischaemic stroke patients and 16 age-matched healthy volunteers were enrolled consecutively in this prospective bi-centre observational study. All acute stroke patients underwent brain CT, optic nerve sonography and transcranial colour-coded duplex sonography (TCCS) at admission within 6 h of stroke onset. The ONSD both 3.0 and 12.0 mm behind the globe using optic nerve sonography were recorded and statistically evaluated, as were age, sex, haemorrhage volume and midline shift measured by CT, and blood flow velocities in both middle cerebral arteries using TCCS. Results: In acute ICH patients, a significant enlargement of ONSD was detected (p<0.0083). The best cut-off point to predict ICH volume >2.5 cm 3 was the relative ONSD enlargement of >0.66 mm (>21 %), with 90.3% accuracy and kappa coefficient 0.760 (95% CI 0.509 to 1.000). Conclusions: Sonographically measured enlargement of the ONSD may already be detectable in the hyperacute stage of increased intracranial pressure.